Douglas Kenrick - LI, Norman P. (Institutional Knowledge at Singapore Management University, 2020)
Douglas Kenrick is a president’s professor of social psychology at Arizona State University (ASU). He received a BA in psychology from Dowling College (1970) and a PhD (1976) in social psychology from Arizona State University under the tutelage of Robert Cialdini. Kenrick then served as an assistant professor of psychology at Montana State University before coming back to ASU. In 2018–2019, Kenrick served as president of the Human Behavior and Evolution Society. He has authored over 200 highly cited academic articles, 2 textbooks, and 2 popular books – Sex, Murder, and the Meaning of Life (2011) and The Rational Animal (2013, with Vlad Griskevicius) – as well as numerous edited volumes and invited book chapters. He is well known among colleagues, students, collaborators, and anyone who has attended any of his talks, as being extremely insightful and funny. His wit and guts are undisputedly unmatched by any academic. In a now-legendary 2000 Human Behavior and Evolution Society plenary presentation, Kenrick delivered the entire 45-min talk in a deeply-southern Baptist preacher’s accent and left a standing-room-only audience rolling with laughter in their seats and in the auditorium aisles.